Bridging Gender Barriers: The Working Environment, Challenges, and Leadership Opportunities for Women Civil Engineers - Thapa, Chetna (PAAN Journal, 2026)
Nepal's highly embedded patriarchal ethos has consistently presented engineering, and in particular, civil engineering, as predominantly a male field. This masculine perception has led to structural impediments in keeping women from full participation in the profession. Despite these challenges, Nepali women are increasingly breaking these social barriers and making significant contributions to the field of civil engineering. This study examines issues of women engaged in the civil engineering career in the Department of Roads in Nepal. Addressing the impact of gender stereotypical prejudices, conflict between work and life, and a shortage of opportunities for mentoring. Qualitative and quantitative analysis techniques are employed to report significant barriers and explore how women can better occupy leadership roles. By advocating organizational reforms and supportive policies, this paper also seeks to contribute to establishing a gender-sensitive and equitable workplace for women in the civil engineering profession at the Department of Roads.